Interaction between hypoxia, AKT and HIF-1 signaling in HNSCC and NSCLC: implications for future treatment strategies - Stegeman H; Span PN; Peeters WJ; Verheijen MM; Grénman R; Meijer TW; Kaanders JH; Bussink J (My University, 2022)
Background: Hypoxia is a negative prognostic factor and this study investigated the relationship between hypoxia, hypoxia inducible factor 1 (HIF-1) and AKT signaling in head and neck squamous cell carcinoma (HNSCC) and non-small-cell lung cancer (NSCLC). Results/methodology: pAKT was induced by hypoxia (0.5% O2) in a part of HNSCC (3/4) and squamous (2/3) and adenocarcinoma (1/3) NSCLS lines. AKT-inhibitor MK-2206 reduced hypoxic HIF-1 signaling in most HNSCC cell lines. This reduction did not correlate with hypoxic induction of pAKT or with sensitivity to MK-2206 under hypoxia. Patient biopsies revealed a hypoxia-induced expression pattern of pAKT in HNSCC (n = 16), which was not observed in squamous cell (n = 34) or adenocarcinoma (n = 41) NSCLC. Conclusion: The interaction between hypoxia, HIF-1 and AKT signaling varies between tumor types and histologies, which could significantly affect response to targeted therapies.